Hubungan Kekuatan Otot Lengan Dengan Kemampuan Chest Pass Peserta Ekstrakulikuler SMP Negeri 6 Lubuklinggau - Yolanda, Anisa (e-SPORT: Jurnal Pendidikan Jasmani, Kesehatan dan Rekreasi, 2024)
This research aims to determine whether there is a relationship between Arm Muscle Strength and Chest Pass Ability, arm muscle power with the accuracy of chest pass ability. The research method used a test technique. The research population consisted of 20 extracurricular students from SMP Negeri 6 Lubuklinggau, and the sample in this study was 20 basketball extracurricular students from SMP Negeri 6 Lubuklinggau using the simple correlation technique. The research instruments used were tests and measurements of push-ups and chest pass tests. Data analysis was done using correlation and multiple regression at a significant level of 5% (0.05). The research results showed a correlation between push-up coordination and arm muscle strength, arm muscle strength, and chest pass ability. The conclusion of this study is that push-ups are related to arm muscle strength and arm muscle strength is related to chest pass ability, with a calculated F value = 28.184 and a critical F value = 4.20. Keywords: Arm Muscle Strength, Chest Pass Ability.